Logistical cities in peripheral areas - Pretorius, Marius Pieter (University of the Free State, 2013)
𝑬𝒏𝒈𝒍𝒊𝒔𝒉 This thesis is the first study in South Africa to explore the concept of logistics cities in peripheral areas with in the context of local economic development. Although the term logistics city is used freely to denote cities in which logistics forms an important part of their economic base − as is the case in Dubai, Shangai and Zaragoza − the body of academic literature on the topic is extremely limited. The logistics city concept was formulated in Australia as an academic concept from approximately 2006 onwards. In South Africa, there is seemingly a tendency among decision makers to regard the mere existence of an airport, especially its potential transformation into an air-freight hub, as a possible local economic development initiative. The aim of this study was to evaluate Upington (as a peripheral area within the South African economy) and its ability to utilise the Upington International Airport as a local economic development initiative, specifically from the perspective of a logistics city. The study analysed the latest theoretical developments in location theory, specifically the new economic geography (NEG) and cluster theory as a basis of the logistics city. The NEG, which was developed in the 1990s in response to the changes brought about by globalisation and the strides made in technology, argues that − theoretically at least − peripheral regions could grow through the development of logistic clusters at the location of an airport. In addition, given the current capacity problems at OR Tambo International Airport, the NEG should pave the way for the development of a logistics facility at the UIA, the more so from the perspective of the logistics city concept. The study confirmed that, in spite of the theoretical opportunities presented by the NEG, the logistics city concept and the incorporation of an air-freight hub in provincial policy and strategy documents, air-freight hub development is still fundamentally dependent on market conditions and that the existence of well-developed airport infrastructure alone is not sufficient reason for transforming a regional airport in a peripheral area into a logistics facility. The study further showed that despite the increasing range of local economic development (LED) research in South Africa, academic literature focusing on the relationship between air-freight transport, logistics and LED is virtually non-existent. Moreover, the study showed that LED efforts are seriously hampered by a number of issues, such as the lack of assimilation of the logistics and air-freight industries into local economic development policy and plans, a lack of capacity at the institutional level, the lack of integrated planning between the spheres of government, the LED stakeholders, parastatals, agencies and the private sector and also the lack of clear policies on the developmental role of regional airports in South Africa. The dominance of ACSA, and the company’s own lack of a strategic focus on regional airports, has also been shown to be problematic. The study further demonstrated efficient logistics to be an important determinant of a country’s competitiveness and that South Africa may lose competiveness because both of high logistics costs and low logistics performance levels. The study also showed that there is generally a lack of accurate information and data on logistics and air freight in South Africa, particularly at the regional and the local level, which makes effective and integrated planning even more difficult.

𝑨𝒇𝒓𝒊𝒌𝒂𝒂𝒏𝒔 Hierdie proefskrif is die eerste Suid-Afrikaanse studie om die konsep van logistieke stede in randgebiede binne die konteks van plaaslike ekonomiese ontwikkeling te verken. Ten spyte daarvan dat die term logistieke stad vryelik gebruik word ter beskrywing van stede soos Dubai, Sjanghai en Zaragoza, waar logistieke aktiwiteite 'n belangrike deel van die ekonomiese grondslag vorm, is die akademiese literatuur oor die onderwerp baie beperk. Die konsep van 'n logistieke stad is vanaf omtrent 2006 en verder as akademiese konsep in Australië ontwikkel. In Suid-Afrika is besluitnemers geneig om die blote bestaan van 'n lughawe veral die moontlike ontwikkeling daarvan in 'n lugvragspil as 'n potensiële plaaslike ekonomiese ontwikkelingsinisiatief te beskou. Die doel van die studie was 'n evaluering van Upington as 'n randgebied in die Suid- Afrikaanse ekonomie en sy vermoë om die Upington Internasionale Lughawe as 'n plaaslike ekonomiese ontwikkelingsinisiatief te gebruik, in die besonder vanuit die perspektief van 'n logistieke stad. Die studie bied 'n ontleding van die nuutste teoretiese ontwikkeling in liggingsteorieë, by name die nuwe ekonomiese geografie (NEG) en klusterteorie wat die grondslag van die konsep logistieke stad vorm. Volgens die NEG wat in die 1990's ontwikkel is in reaksie op sowel die veranderings wat globalisering meegebring het as tegnologiese vooruitgang, kan randgebiede wel groei ten minste teoreties deur die vestiging van logistieke klusters by lughawens. Hierbenewens, en gegewe die bestaande kapasiteitsprobleme by die OR Tambo Internasionale Lughawe, behoort die nuwe ekonomiese geografie die weg te baan vir die ontwikkeling van 'n logistieke fasiliteit by die Upington Internasionale Lughawe, veral vanuit die perspektief van die konsep logistieke stad. Die studie bevestig dat ten spyte van die teoretiese geleenthede wat deur die nuwe ekonomiese geografie, die logistieke stad-konsep en die insluiting van 'n lugvragspil in provinsiale beleids- en strategiedokumente gebied word, marktoestande bepalend is in die vestiging van 'n lugvragspil en dat die blote bestaan van infrastruktuur, ongeag hoe goed ontwikkel, nie genoegsame rede bied om 'n streekslughawe in 'n randgebied geleë in 'n logistieke fasiliteit te ontwikkel nie. Die studie dui verder aan dat ongeag die toenemende omvang van navorsing oor plaaslike ekonomiese ontwikkeling, daar feitlik geen akademiese literatuur bestaan wat op die verband tussen lugvragvervoer, logistiek en plaaslike ekonomiese ontwikkeling fokus nie. Die studie dui ook aan dat plaaslike ekonomiese ontwikkelingspogings ernstig belemmer word deur 'n aantal kwessies, waaronder die gebrek aan integrering van die logistieke en lugvragbedrywe in plaaslike ekonomiese ontwikkelingsbeleid en - beplanning, gebrekkige institusionele vermoë, gebrekkige geïntegreerde beplanning tussen die vlakke van regering, die plaaslike ekonomiese ontwikkelingsrolspelers, semistaatsinstellings, agentskappe en die privaat sektor, asook 'n gebrek aan duidelik geformuleerde beleid rakende die ontwikkelingsrol van streeklughawens in Suid-Afrika. Die totale oorheersing van ACSA, tesame met die maatskappy se eie gebrek aan 'n strategiese fokus vir streeklughawens het ook geblyk 'n probleem te wees. Die studie het voorts aangetoon dat doeltreffende logistieke aktiwiteite 'n belangrike determinant van 'n land se mededingendheid is en dat Suid-Afrika van sy mededingendheid kan verloor vanweë sowel hoë logistieke koste as lae logistieke prestasievlakke. Die studie het ook gewys dat daar in Suid-Afrika in die algemeen 'n gebrek is aan noukeurige logistieke en lugvraginligting en -data, veral op die streeks- en plaaslike vlakke, wat effektiewe en geïntegreerde beplanning verder bemoeilik.
Thesis (Ph.D.(Centre for Development Support))--University of the Free State, 2013
Keywords: Upington International Airport; Economic development -- South Africa -- Northern Cape; Logistics; Freight and freightage -- South Africa -- Northern Cape; Airports -- South Africa -- Northern Cape; Cargo handling; Logistics city; Peripheral area; New economic geography; Air-freight hub; Local economic development; Logistics